A Novel Elevated Plus-Maze Procedure to Avoid the One-Trial Tolerance Problem - Schneider, Peggy; Ho, Ying-Jui; Spanagel, Rainer; Pawlak, Cornelius R. (Frontiers in Behavioral Neuroscience, 2011)
The elevated plus-maze (EPM) test is one of the most commonly used behavioral assays to evaluate anxiety-related behavior in rodents. It is an economic test (5 min duration) without prior conditioning of the animals. The critical measure for anxiety is the time spent in the open arms of the maze. A confounding problem of the EPM is the so called one-trial tolerance (OTT), characterized by a marked decrease of open arm exploration in spite of treatment with anxiolytic acting benzodiazepines upon re-exposure to the EPM. This consistent finding is often raised as an evidence for the inappropriateness to re-test rodents in the EPM. However, a reliable re-test paradigm would broaden the usability and effectiveness of this test. Therefore, we tested how an extension of the inter-trial interval to 28 days (instead of the usual 24 h), and an additional change of the testing room would affect the open arm time and other behaviors on the EPM. In two experiments, drug-naive Wistar rats were exposed to the EPM on trial 1, and treated intraperitoneally with either vehicle or midazolam (0.25 mg/kg) 30 min before trial 2. Then, trial 2 (28 days after trial 1) was carried out in either the same testing room (Experiment 1) or in another unfamiliar room (Experiment 2). Twenty-eight days after trial 1 the open arm time of the rats in the vehicle treated control rats of both experimental groups was comparable to that of the first trial, independent of the testing room. Most importantly, we found that the treatment with the benzodiazepine midazolam had a significantly anxiolytic-like (i.e., increase of open arm time) effect in trial 2 only when conducted in the previously unfamiliar testing room (Experiment 2). We suggest that in order to reliably re-test the EPM and to prevent confounding effects due to the OTT, an inter-trial interval of 28 days and a change in testing rooms reinstates anxiolytic-like actions of benzodiazepines.